Non-destructive monitoring system in cassava - Cock, James H.; Moreno Cadena, Leidy Patricia; Toro, M.A.; Arango, Jacobo (Ministerio de Agricultura y Desarrollo Rural, Colombia, 2014)
This non-destructive method provides a means of monitoring the development of the cassava crop under a range of biophysical environments without the need to plant trials specifically for this purpose. The plots established or commercial lots can be monitored nondestructively: therefore any parcel can be monitored. The methodology collects data on the development of the cassava crop and can use this data in understanding the development of the crop, and also to generate, validate and improve the robustness of simulation models cassava. This is the first approximation of the methodology; we encourage users to voice any concerns and suggest ways of improving the non-destructive monitoring system.